(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To describe the process of developing and validating the content of an educational program for training in urostomy self-care, based on scientific evidence, and present an initial feasibility test of its clinical application. Method: The program was developed based on nursing interventions identified in a scoping review and submitted for content validation to a panel of six wound, ostomy, and continence-certified nurses using the Delphi method. Subsequently, its operationalization was assessed through an exploratory feasibility test (single-case study), with data collected for process monitoring using the Urostomy Education Scale (UES). Results: The scoping review identified 114 nursing interventions, supporting the development of a structured educational program comprising five sessions. After its elaboration, it was submitted to a validation process, obtaining a certified nurse agreement rate of 0.8. The feasibility test demonstrated the program’s operationalization and the UES’s sensitivity in monitoring self-care progression (from deficit to autonomy), confirming the relevance of the intervention algorithm for situations of skills stagnation. Conclusion: The developed and validated educational program is a relevant tool for systematizing clinical practice. The feasibility test demonstrated its potential in promoting patient autonomy and monitoring the training process.